A Study of Aspects of Digital Discourse in Nigerian Democratic Space - Opeibi, Tunde; Ademola-Adeoye, Feyi; Adedeji, Kofo (Unilag Journal of Humanities, 2019)
The primary aim of this study is two-fold: one, to situate corpus-based digital political discourse within the field of digital humanities; and, two, to apply computer methodologies to examine the use of web-based platforms for political purposes in Nigeria. It adopts a combination of qualitative and quantitative approaches as demonstrated in Corpus-Based Discourse Model and Computer-Mediated Discourse Analysis (CMDA). Both methodological and analytical methods used rely on the use of some internet-based computer applications and corpus analytical tools such as SketchEngine, Topsy and AntCorc3.4. The data set was collected through media monitoring and online data harvesting strategies from the Internet, webpages and social media networks of key political actors and stakeholders in Nigeria, and extracted from a specialised corpus named Corpus of Nigeria New Media Discourse in English (CONNMDE). The application of computer methodologies to the analysis of digital political text is presented as a new research orientation in digital humanities that can improve scholarship and research breakthroughs. Digital media technologies such as Facebook and Twitter can indeed help citizens acquire new skills which can foster creativity, boost engagement and enhance capacity. These may help the country solve problems which can galvanize economic development. The study further argues that widespread use of Internet-based technologies for political purposes can accelerate our progress towards a sustainable and strong democracy. They can indeed transform our national political narratives, promote participation, transparency, accountability and improve national development index